Images Segmentation Based on Fast Otsu Method Implementing on Various Edge Detection Operators - Hameed M. Abdul jabar; Amal J. Hatem; Taghreed A. Naji (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
The present work aims to study the effect of using an automatic thresholding technique to convert the features edges of the images to binary images in order to split the object from its background, where the features edges of the sampled images obtained from first-order edge detection operators (Roberts, Prewitt and Sobel) and second-order edge detection operators (Laplacian operators). The optimum automatic threshold are calculated using fast Otsu method. The study is applied on a personal image (Roben) and a satellite image to study the compatibility of this procedure with two different kinds of images. The obtained results are discussed.